Menelusuri Simbolisme Gerak: Kritik dan Analisis Tari Balada Cenderawasih dalam Representasi Budaya Papua - Ilham Mustain Murda, Muhammad (Pusat Riset dan Inovasi Nasional, 2024)
The Ballad of the Bird of Paradise is a new form of dance inspired by the behavior of the bird of paradise, a bird endemic to Papua that has long been recognized as a symbol of natural beauty and ecosystem preservation. This dance performance features two main characters, a male and a female bird. Conceptually, the two should display distinct movement expressions: the male character is presented through agile, dynamic, and captivating movements, while the female character emphasizes gentleness, elegance, and harmony of movement. These differences in expression serve not only aesthetic purposes but also hold symbolic meanings that reinforce the cultural values ​​and philosophy of this dance. However, analysis of several performances, both live and recorded and displayed on social media, shows that the movement differentiation between the male and female characters is often inconsistent. This results in the symbolism that is at the heart of the Ballad of the Bird of Paradise dance being less visible, thus the depth of the intended cultural meaning is not fully conveyed to the audience. In fact, efforts to preserve and standardize the Balada Cenderawasih dance have been undertaken by the Papua Arts Council (DKTP), including through a 2016 seminar discussing choreographic standards and the meaning of the dance. However, the implementation of these standardizations in the field still faces various obstacles, both in terms of dancer understanding and the continuity of training. Based on these findings, this study recommends the importance of strengthening the differentiation of movements between male and female characters in each choreography. In addition, increased training intensity, artistic supervision, and promotion of the Balada Cenderawasih dance at the national level are needed.